Transformational Leadership and Work-Life Balance on Job Satisfaction: The Mediating Role of Employee Engagement - Arum Puspita; Au Yong Hui Nee (Universitas 17 Agustus 1945 Semarang, 2026)
This study investigates the effects of transformational leadership and work-life balance on job satisfaction, with employee engagement as a mediating variable, within the context of modern organizational work environments. Increasing job demands and performance pressures have raised concerns regarding employee psychological well-being, yet previous empirical findings on how leadership and work-life balance influence job satisfaction remain inconsistent. Therefore, this research aims to examine whether employee engagement serves as a psychological mechanism that explains the relationship between transformational leadership, work-life balance, and job satisfaction. A quantitative research approach was employed, with data collected through structured questionnaires using a Likert scale. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to test both direct and indirect relationships among variables. The results indicate that transformational leadership has a significant positive effect on employee engagement, which subsequently has a strong positive influence on job satisfaction. However, work-life balance does not demonstrate a significant direct or indirect effect on job satisfaction in this research context. Furthermore, employee engagement is proven to fully mediate the relationship between transformational leadership and job satisfaction. In conclusion, this study highlights employee engagement as a key psychological pathway through which transformational leadership enhances job satisfaction and provides practical implications for organizations to prioritize leadership development aimed at strengthening employee engagement.